KEADILAN EKONOMI DALAM HUKUM BISNIS ISLAM: PERSPEKTIF TERHADAP LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN TIDAK SEHAT - Muhammad, Fadhilah; Fadhilah, Haidar Naufal; Hidayat, Muhammad Iltizam (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
Monopolistic practices and unfair competition, such as cartels, market domination, and price discrimination, threaten economic justice in Indonesia, especially in the digital economy dominated by large tech platforms. Law No. 5 of 1999 aims to curb these issues, but enforcement faces challenges due to complex digital markets, lobbying by major businesses, and limited institutional resources. Islamic business law offers an ethical complement through principles like ihtikar (prohibiting hoarding to manipulate prices) and maslahah (prioritizing public interest). This study examines monopolistic practices from an Islamic perspective, analyzing alleged monopolies by Google in Indonesia (2024) and a state-owned enterprise in the energy sector. Using a normative approach with qualitative analysis, it finds that Islamic principles can enhance anti-monopoly law enforcement through moral frameworks, ethical education, and public benefit evaluations. The study recommends integrating Islamic values into public campaigns, legal enforcement, and SOE regulations to promote sustainable economic justice in Indonesia. Keywords : Monopoly, Unfair Competition, Islamic Business Law, Economic Justice, Digital Monopoly.